Natural Resources and Indigenous People’s Livelihood Strategies: A Case Study of Human Communities in the Headwaters of Engkari River, Sri Aman, Sarawak, Malaysia - Spencer Empading, Sanggin; Neilson Ilan, Mersat; Wong, Swee Kiong; Mohamad Suhaidi, Salleh; Mohd. Azizul Hafiz, B. Jamain; Ahi, Sarok; Peter, Songan (Academic Star Publishing Company, 2016)
This paper discusses the livelihood strategies and the environment in which the Iban of Rumah Jaong of the headwaters of Engkari River survives on and the challenges faced by its residents. The livelihood of the small Iban community depends on the natural resources for survival. Rivers serve as the source of food, domestic water supply and means of transportation. Forests, on the other hand, serve as source of food, timber and building materials, and to a lesser extent, as a people’s hunting ground. To many outsiders, life in the headwaters of Engkari River is easily perceived as difficult and very challenging. However, for the local residents of a community living in the interior and remote part of Sarawak, such as in headwaters of Engkari river, life is considered ‘normal’ where the practice of mixed farming consisting of shifting cultivation of hill rice and with small plots of rubber and/or pepper garden seems sufficient to sustain the people’s livelihood, at least for now.